Human Origin Lactobacillus casei Isolated from Indonesian Infants Demonstrating Potential Characteristics as Probiotics in vitro - W. Widodo; Tiyas Tono Taufiq; Ety Aryati; Asih Kurniawati; Widya Asmara (Indonesian Journal of Biotechnology, 2012)
The aim of this experiment was to isolate and identify Lactic Acid Bacteria (LAB) from infant faecesand subsequent evaluation of its potential probiotics. LAB was isolated from faeces of infants who consumedbreast milk as the only source of diet on L-cysteine-supplemented MRS Agar, and incubated on 37oC for 48hours. Colonies grew on this media were then identifi ed based on morphological, physiological and molecularapproaches. Morphological and physiological identifi cations based on Gram staining, shape, motility, sporeformation, catalase, CO2 and NH3 production, and the ability to grow on temperature at 10oC and 45oC.Molecular identifi cation based on the amplifi cation of 16S rRNA gene. The potential application of selectedisolates for probiotics was evaluated based on the ability to grow on media with low pH and the additionof 0.5% bile salts, the ability to inhibit the growth of pathogenic Bacillus cereus and Eschericia coli, and in vitroadherence ability. On the basis of morphological, physiological and molecular analysis of 16S rRNA gene, itwas concluded that the selected isolate 1AF was a strain of Lactobacillus casei. Evaluation of probiotic in vitro showed that 60.4% of cells were resistant to pH 2.0 for 90 minutes. Survival of isolate 1AF after growing at0.5% bile salts was 70.8%. The selected isolate 1AF showed the ability to inhibit the growth of Eschericia coli and Bacillus cereus with inhibitory zone of 12.00±1,00 and 15.33±1.53 mm, respectively. In vitro study on theadherence value of isolate to solid plate was found at 46.5%. It is concluded that Lactobacillus casei isolate 1AFis a potential candidate as probiotics and subject to further in vivo evaluation.